In the eye of the beholder? Leader and employee ratings of leadership across individuals, organizations, and service areas - Jensen, Ulrich Thy; Jacobsen, Christian Bøtcher (Politica, 2016)
Leadership has become an important topic in public management research, and most empirical studies of leadership apply measures based on survey responses by managers and employees. A consistent finding is, nonetheless, that there is great variation in assessments of leadership, and it has been suggested that these variations can be explained by factors on three levels: the individual level within an organization, the organizational level, and the sector level. However, there is very little empirical knowledge about variation at these levels, and the article therefore investigates how two important types of leadership – transformational leadership and transactional leadership – vary at these three levels. We apply survey data from 541 managers and their 8,515 employees, from eight different service areas. The analyses show that the main variation in leadership ratings is within organizations, but significant variation also exists between organizations and service areas. Finally, leaders rate their own leadership more favorably than their employees do.